CT Arteriography and Venography in Pulsatile Tinnitus: Preliminary Results - Krishnan, A.; Mattox, D.E.; Fountain, A.J.; Hudgins, P.A. (American Journal of Neuroradiology, 2006)
BACKGROUND AND PURPOSE: Pulsatile tinnitus (PT), a common disorder, can be caused by a variety of otologic and vascular lesions. Various imaging modalities, including CT, MR imaging and angiography, and conventional angiography, have been used in the assessment of PT. Ideally, a single imaging study to evaluate for the largest variety of etiologies would be optimal. In our study, we examine the potential for CT arteriography and venography (CTA/V) in the evaluation of PT.METHODS: Sixteen patients with PT were prospectively evaluated by an otolaryngologist, had a normal otologic examination, and were referred for a CTA/V. All examinations were performed on a 16-section multidetector CT. The carotid bifurcations, internal carotid artery course, transverse and sigmoid sinuses, jugular foramen, internal jugular vein, sella turcica, and temporal bones were evaluated.RESULTS: Seven of the 16 patients had lesions on CTA/V that could account for their PT. Examples of pathologic conditions in the series included a significantly dominant venous system, a venous diverticulum with stricture, and a transverse sinus stenosis.CONCLUSIONS: Preliminary findings indicate that CTA/V can be a valuable imaging tool in the assessment of PT. With this technique, arterial, venous, middle, and inner ear causes of PT can be excluded.